Effects of oenological tannins on aroma release and perception of oxidized and non-oxidized red wine: A dynamic real-time in-vivo study coupling sensory evaluation and analytical chemistry. (15th March 2022) - Pittari, Elisabetta; Piombino, Paola; Andriot, Isabelle; Cheynier, Véronique; Cordelle, Sylvie; Feron, Gilles; Gourrat, Karine; Le Quéré, Jean-Luc; Meudec, Emmanuelle; Moio, Luigi; Neiers, Fabrice; Schlich, Pascal; et al.
Highlights: A dynamic sensorial evaluation of 6 wines is coupled to dynamic aroma release recording. Addition of ellagitannin extract impacts the dynamic of sensations of oxidized wine. Addition of ellagitannin extract impacts the length of aroma release in mouth. Addition of ellagitannin extract preserves fruitiness under oxidative conditions. Abstract: Addition of oenological tannins claims to have a positive impact on wine stability, protection from oxidation and likely sensory persistence. However, their role on red wine aroma during oxidation is controversial. The present study aims at investigating the effect of addition of oenological tannins on wine flavour (mainly aroma) before and after air exposure. Temporal Dominance of Sensations, a dynamic sensory evaluation, was coupled with a dynamic chemical measurement (nosespace analysis) using a Proton-Transfer-Reaction Mass-Spectrometer connected to the nasal cavity of 17 assessors. Results showed that the oxidation of a non-oaked Pinot Noir red wine decreases the fruity aroma dominance and increases the maderised and prune one. A contextual decrease of the fruity ethyl decanoate and increase of oxidative Strecker aldehydes are observed. Ellagitannins but not proanthocyanidins preserved perception of fruitiness and prevented increase of maderised notes. Moreover, ellagitannins increase the aroma persistence mainly in the non-oxidized wine.